Does firm size matter? Evidence on the impact of liquidity constraint on firm investment behavior in Germany - David B. Audretsch; Julie Ann Elston (Hamburg Institute of International Economics (HWWA), 2000)
This paper examines the link between liquidity constraints and investment behavior for German firms of different sizes from 1970 to 1986. Results indicate that medium sized firms appear to be more liquidity constrained in their investment behavior than either the smallest or largest firms in the study, suggesting that the unique German infrastructure designed to assist the small firm has indeed succeeded in alleviating, to some degree, such liquidity constraints. Findings also support the hypothesis that the emerging competition and internationalism which characterized the German financial markets in the 1980's, have been improving access to capital for some groups of firms. – – Dieser Beitrag untersucht die Beziehung zwischen Liquiditätsbeschränkungen und Investitionsverhalten deutscher Unternehmen unterschiedlicher Größen im Zeitraum 1970 bis 1986. Die Ergebnisse deuten darauf hin, dass das Investitionsverhalten mittlerer Unternehmen stärker von der Liquiditätsseite her beschränkt ist als das der in der Untersuchung berücksichtigten kleinen und großen Unternehmen. Dies spricht dafür, dass die besondere deutsche Infrastruktur, die auf eine Unterstützung kleiner Unternehmen ausgerichtet ist, derartige Liquiditätsbeschränkungen mit Erfolg in gewissem Maße gelockert hat. Die Ergebnisse unterstützen auch die Hypothese, dass der stärkere Wettbewerb und die Internationalisierung, die die deutschen Finanzmärkte in den achtziger Jahren kennzeichneten, einigen Gruppen von Unternehmen den Zugang zu Kapital verbesserten.
Keywords: 330; Investition; Betriebsgröße; Verschuldungsrestriktion; Tobin's q; Schätzung; Deutschland